Composition and Morphological Characteristics of Extracellular Polymeric Substances of Different Tolerant Bacteria Under Perfluorobutanesulfonic Acid (PFBS) Stress - Rui Tang; Lina Sun; Guo Yu; Jiayao Xu; Qing Luo; Xiaoxu Wang; Luge Rong (Toxics)
This investigation studies the properties and composition of extracellular polymeric substances (EPS) of the four tolerant bacterial strains [NH (Cellulosimicrobium cellulans), TH, YH, and HE (Pseudomonas aeruginosa)] under perfluorobutanesulfonic acid (PFBS) stress. The strains were acquired from athickened sludge in a fluorine chemical park. Each strain’s EPS were isolated by heating and centrifugation, and their growth, metabolic activity, and EPS alteration research pre- and post-stress were assessed and compared. The strain type was identified by morphological observation and 16S rDNA gene sequence analysis. Under PFBS (100 μg·L−1) stress, the four tolerant strains NH, TH, YH, and HE showed 38.10%, 29.26%, 35.92%, and 30.48% removal of PFBS on day 4, respectively, and the strain’s EPS had a substantial impact on main component protein (PR) and polysaccharide (PS) contents. The NH microorganism’s ability to metabolize organic matter was markedly stronger; it had a higher quantity, and its impact on main EPS content was greater than the other three tolerant strains. The three-dimensional excitation–emission matrix results showed marked alterations in tryptophan and aromatic protein peaks in the tolerant strain’s EPS. Furthermore, the FTIR analysis showed that the intensity of the functional groups in the proteins (-OH, C=O, -NH, and -CN) and the polysaccharides (-OH, C-O-C, and C-O) changed significantly. This investigation indicated that the proteins and polysaccharides of the tolerant strain’s EPS could provide more binding sites for PFBS adsorption, where the NH strain had the best biosorption capacity. This research provides a theoretical basis for elucidating efficient biosorbents.